2023
DOI: 10.1186/s12877-023-04106-7
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunity in mobility among older adults – key determinant identification

Abstract: Background Attention is focused on the health and physical fitness of older adults due to their increasing age. Maintaining physical abilities, including safe walking and movement, significantly contributes to the perception of health in old age. One of the early signs of declining fitness in older adults is limited mobility. Approximately one third of 70-year-olds and most 80-year-olds report restrictions on mobility in their apartments and immediate surroundings. Restriction or loss of mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 92 publications
(132 reference statements)
1
1
0
Order By: Relevance
“…Notably, our finding that the utilization of food assistance programs decrease with age in model 1 correlates with a previous study [42]. Older adults may be challenged by mobility constraints [43] and lack of awareness and information [44] to physically access food assistance programs. Our findings on race/ethnicity and use of food assistance programs align with a previous study that reported that Asians and Hispanic are among the races and ethnicity that least access SNAP [45,46] and will least likely use this type of food resource.…”
Section: Discussionsupporting
confidence: 85%
“…Notably, our finding that the utilization of food assistance programs decrease with age in model 1 correlates with a previous study [42]. Older adults may be challenged by mobility constraints [43] and lack of awareness and information [44] to physically access food assistance programs. Our findings on race/ethnicity and use of food assistance programs align with a previous study that reported that Asians and Hispanic are among the races and ethnicity that least access SNAP [45,46] and will least likely use this type of food resource.…”
Section: Discussionsupporting
confidence: 85%
“…As Social Learning Theory implies, individual observation learning is an interaction between individual behavior, intrinsic factors, and the environment. The change in personal behavior is determined by the outcome of interactions between individuals and the environment [ 31 ]. According to the research, older adults who recognize their gap in sports health knowledge or skills will be driven to pursue these knowledge and skills under the catalysis of community culture.…”
Section: Discussionmentioning
confidence: 99%
“…However, alongside these advancements come legitimate concerns regarding the safety and reliability of the materials and components used in their construction. The quality and integrity of mobility aids are paramount in safeguarding users from potential hazards and mitigating the risk of serious injuries or accidents [50,51].…”
Section: Table 2: the Current Mobility Aids On The Market And Their B...mentioning
confidence: 99%